2003
DOI: 10.1590/s0100-29452003000200006
|View full text |Cite
|
Sign up to set email alerts
|

Temperaturas efetivas para a dormência da macieira(Malus domestica Borkh)

Abstract: As cultivares de macieira exigem diferentes requerimentos em frio, ou seja, o total de horas abaixo de um limite de temperatura do ar, porém são poucas as informações sobre quais temperaturas são mais eficientes para superar a dormência. As cultivares de macieira Condesa, Baronesa, Daiane, Imperatriz, Fuji e Gala foram estudadas quanto à quantidade de frio e as temperaturas do ar para a indução da brotação. O delineamento experimental foi o inteiramente casualizado, no esquema fatorial, com seis cultivares, ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
14

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 6 publications
0
8
0
14
Order By: Relevance
“…Putti et al (2003aPutti et al ( , 2003b) also obtained low percentage of budbreak in apple cultivars with medium and high chilling requirement, even with high chilling exposure. The first buds overcome dormancy may influence the intensity of the other dormant buds still dormant, where the early budbreak in terminal buds inhibits the growth of other buds in a typical case of apical dominance.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Putti et al (2003aPutti et al ( , 2003b) also obtained low percentage of budbreak in apple cultivars with medium and high chilling requirement, even with high chilling exposure. The first buds overcome dormancy may influence the intensity of the other dormant buds still dormant, where the early budbreak in terminal buds inhibits the growth of other buds in a typical case of apical dominance.…”
Section: Resultsmentioning
confidence: 89%
“…The differential effect of temperatures during dormancy period between the apple cultivar on budbreak indicate that cultivars with lower chilling requirement (Castel Gala) may supply its physiological necessities, may be capable to budburst, even when subjected to higher temperatures when compared to cultivars with higher chilling requirement (Royal Gala). Putti et al (2003b), using single node cutting biological test, also observed that the effectiveness of temperature to overcome dormancy varies among apple cultivars, where cultivars with lower chilling requirement have effective temperatures higher than cultivars with higher chilling requirement. The same response was obtained by Chavarria et al (2009), using the grafted twigs methodology in peach trees, where the temperatures of 15ºC during winter promoted satisfactory percentage of budbreak and flowering in low chill cultivars, such as 'Turmalina' cultivar.…”
Section: Resultsmentioning
confidence: 94%
“…According to Berlato and Sutilli (1976), a flaw in some mathematical models is that they do not discriminate the Tb of each species or genotype (early-, intermediate-, or late-maturing cultivar) as a basis for accurate modeling of plant phenology. Putti et al (2003) and Anzanello (2012) report possible differences in Tb among cultivars within a single fruit species. They found that apple cultivars contrasting in thermal requirement during dormancy show different intervals of effective cold temperatures -higher (3 to 12°C) for genotypes with low winter chilling requirements, and lower (3 to 6°C) for those with high chilling requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Diversas espécies frutíferas de clima temperado vêm sendo estudadas para conhecimento dos aspectos envolvidos na entrada, manutenção e liberação da endodormência como a macieira (Carvalho & Zanette, 2004b;Putti et al, 2003), a pereira (Oliveira et al, 2008) e o pessegueiro (Oliveira Filho & Carvalho, 2003). O caquizeiro é uma cultura pouco estudada em relação à dormência e os resultados não convergem para um entendimento claro da sua fisiologia, pois enquanto Mowat (1995) concluiu que gemas de caquizeiro podem sair da dormência mesmo sem ocorrência de frio, Faquim et al (2007) evidenciaram que as gemas da caquizeiro necessitam de 504 h de frio para atingir 100% de brotação de gemas terminais e laterais.…”
Section: Introductionunclassified